Maltreatment experiences and mental health indicators among elite athletes - Willson, E.; Buono, S.; Kerr, G.; Stirling, A. (Psychology of Sport and Exercise, 2023)
This study explored the relationships between athletes` experiences of maltreatment and mental health indicators. Canadian National Team athletes completed an online, anonymous survey that assessed reported experiences of maltreatment (psychological, physical, sexual harm and neglect), and mental health indicators of well-being, eating disorders and self-harming behaviours. All forms of maltreatment had a significant, positive correlation with eating disorder and self-harming behaviours, and a negative correlation with well-being. The relationships between maltreatment and mental health indicators differed based on identity characteristics of the athletes. Further work is needed on the prevention and intervention of maltreatment in sport to reduce the behaviours associated with negative health outcomes.